DESIGN OF ENGLISH VOCABULARY PICTURES CARD MEDIA FOR TEACH VOCABULARY AT ELEMENTARY SCHOOL - Ramadhan, Firman Aulia; Wahono, Suparwoto Sapto; Muhith, Abd (ATTA`DIB, 2023)
This research focuses on the design of media english vocabulary pictures cards aimed at class IV-A at MIN 6 Jembrana Bali to teach English vocabulary. the need for the development of learning media that supports interesting English learning and not only that the media used to teach English in class IV-A min 6 jembrana is not suitable for use, therefore researchers developed media english vocabulary pictures cards. but the research only focuses on media design. The research method used in this research is research and development or better known as Development Research using the ADDIE model. Data collection tools in this research are observation, interview, questionnaire and documentation. Data sources in the study are divided into qualitative and quantitative data. The design of English Vocabulary Pictures card Media is made based on the needs analysis which includes the characteristics of students and students' interest in learning media.